Organizational structure, risk-based capital requirements, and the sales of downgraded bonds - Lu, Erin P.; Lai, Gene C.; Ma, Qingzhong (Journal of Banking & Finance, 2017)
Using bond downgrades as external shocks to life insurers’ asset risk, we document several findings of the impact of organizational structure and risk factors on investment risk taking. First, we find that mutual insurers and widely-held stock insurers are more likely to sell downgraded bonds than are closely-held stock insurers. Second, we find evidence that insurers are less likely to sell downgraded bonds that remain in the same rating class than bonds downgraded to a lower rating class. The result implies that insurers sell downgraded bonds mainly because of additional capital charge is imposed, not because of downgrade itself. In other words, risk factors in risk-based capital regulation do matter on life insurers’ investment risk taking. Finally, we find that life insurers might be reluctant to sell downgraded bonds at fire-sale prices during the 2008–2009 financial crisis.